Outcome measures in MMN revisited: further improvement needed. Issue 3 (September 2015) - Pruppers, Mariëlle H. J.; Draak, Thomas H. P.; Vanhoutte, Els K.; Van der Pol, W‐Ludo; Gorson, Kenneth C.; Léger, Jean‐Marc; Nobile‐Orazio, Eduardo; Lewis, Richard. A.; van den Berg, Leonard H.; Faber, Catharina G.; Merkies, Ingemar S. J.; on behalf of the PeriNomS study group; et al.
Abstract The objectives of this study were to provide an overview of the outcome measures (OMs) applied in clinical trials in multifocal motor neuropathy (MMN) and to determine the responsiveness of a core set of selected OMs as part of the peripheral neuropathy outcome measures standardization (PeriNomS) study. The following OMs were serially applied in 26 patients with newly diagnosed or relapsing MMN, receiving intravenous immunoglobulin (assessments: T0/T3/T12 months): 14 muscle pairs MRC (Medical Research Council) scale, the Neuropathy Impairment Scale motor‐subset, a self‐evaluation scale, grip strength, and MMN‐RODS© (Rasch‐built overall disability scale). All data, except the grip strength, were subjected to Rasch analyses before determining responsiveness. For grip strength, responsiveness was examined using a combined anchor‐ (SF‐36 question‐2) and distribution‐based (½ × SD) minimum clinically important difference (MCID) techniques, determining the proportion of patients exceeding both the identified cut‐offs. For the remaining scales, the magnitude of change for each patient on each scale was determined using the MCID related to the individual SE (responder definition: MCID‐SE ≥ 1.96). Overall, a great assortment of measures has been used in MMN trials with different responsiveness definitions. For the selected OMs, responsiveness was poor and only seen in one fourth to one third of the patients, the grip strength being more responsive. Despite the efforts taken to standardize outcome assessment, further clinimetric responsiveness studies are needed in MMN.